1980
DOI: 10.1017/s0022143000010364
|View full text |Cite
|
Sign up to set email alerts
|

Does the Permanent Creep-Rate of Polycrystalline Ice Increase with Crystal Size?

Abstract: ABSTRACT. Uniaxial compression creep tests were p erformed on a rtificial and natural polycrystalline ices at tempera tures near -7°C . The grain-size range investigated was from I to 10 mm. C ontrary to previous results, the p ermanent creep-ra te was not found to in crease with crystal size. Only the transien' t creep appears to b e sensitive to variations in crystal size.R EsuME . L a vitesse du j1uage stationnaire de la glace poiyeristalline erolt elle avee la taille des eristaux? Des experiences d e fluag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Moreover, the results of these tests suggest that finegrained polycrystalline ice may, as a result of more rapid recrystallization, approach steady-state tertiary creep more rapidly than coarser-grained ice and support earlier observations (e.g. Duval and Le Gac, 1980; Jacka, 1984). Both the polycrystalline and layered ice exhibited approximately the same ductility in the tertiary creep regime.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, the results of these tests suggest that finegrained polycrystalline ice may, as a result of more rapid recrystallization, approach steady-state tertiary creep more rapidly than coarser-grained ice and support earlier observations (e.g. Duval and Le Gac, 1980; Jacka, 1984). Both the polycrystalline and layered ice exhibited approximately the same ductility in the tertiary creep regime.…”
Section: Discussionsupporting
confidence: 84%
“…The results here also support the conclusions of other workers (e.g. Duval and Le Gac, 1980; Jones and Chew, 1983; Jacka, 1984), who found that the creep rate was independent of crystal size.…”
Section: Mechanical Behavioursupporting
confidence: 92%
“…As already mentioned, ~ is very small in ice. Although the grainsize dependence of in ice polycrystals from monotonic loading tests is still unexplored, Duval and co-workers [118,119] reported a decreasing primary creep rate with decreasing grain size that might be related with such Hall-Petch mechanism [16].…”
Section: Grain Boundariesmentioning
confidence: 99%
“…These experiments give some insight into more complicated histories (Bindschadler and others, 2013). Similarly the effect of strain rate and initial grain size in pure ice may influence primary creep rates, whereas subsequent tertiary creep appears to be unaffected by the initial grain size (Duval and Le Gac, 1980). However, there is still a lack of data on grain size effects in ice containing dispersed phases, which can be explained by arguments related to the operation of dislocation mechanisms rather than from elastic anisotropy (Schulson and Duval, 2009).…”
Section: Introductionmentioning
confidence: 99%